Multiple Transceptors for Macro- and Micro-Nutrients Control Diverse Cellular Properties Through the PKA Pathway in Yeast: A Paradigm for the Rapidly Expanding World of Eukaryotic Nutrient Transceptors Up to Those in Human Cells - Steyfkens, Fenella; Zhang, Zhiqiang; Van Zeebroeck, Griet; Thevelein, Johan M. (Frontiers in Pharmacology, 2018)
The nutrient composition of the medium has dramatic effects on many cellular properties in the yeast Saccharomyces cerevisiae. In addition to the well-known specific responses to starvation for an essential nutrient, like nitrogen or phosphate, the presence of fermentable sugar or a respirative carbon source leads to predominance of fermentation or respiration, respectively. Fermenting and respiring cells also show strong differences in other properties, like storage carbohydrate levels, general stress tolerance and cellular growth rate. However, the main glucose repression pathway, which controls the switch between respiration and fermentation, is not involved in control of these properties. They are controlled by the protein kinase A (PKA) pathway. Addition of glucose to respiring yeast cells triggers cAMP synthesis, activation of PKA and rapid modification of its targets, like storage carbohydrate levels, general stress tolerance and growth rate. However, starvation of fermenting cells in a glucose medium for any essential macro- or micro-nutrient counteracts this effect, leading to downregulation of PKA and its targets concomitant with growth arrest and entrance into G0. Re-addition of the lacking nutrient triggers rapid activation of the PKA pathway, without involvement of cAMP as second messenger. Investigation of the sensing mechanism has revealed that the specific high-affinity nutrient transporter(s) induced during starvation function as transporter-receptors or transceptors for rapid activation of PKA upon re-addition of the missing substrate. In this way, transceptors have been identified for amino acids, ammonium, phosphate, sulfate, iron and zinc. We propose a hypothesis for regulation of PKA activity by nutrient transceptors to serve as a conceptual framework for future experimentation. Many properties of transceptors appear to be similar to those of classical receptors and nutrient transceptors may constitute intermediate forms in the development of receptors from nutrient transporters during evolution. The nutrient-sensing transceptor system in yeast for activation of the PKA pathway has served as a paradigm for similar studies on candidate nutrient transceptors in other eukaryotes and we succinctly discuss the many examples of transceptors that have already been documented in other yeast species, filamentous fungi, plants, and animals, including the examples in human cells.